Hubungan konsep diri dengan mekanisme koping pada pasien post operasi glaukoma di poli mata RSUD Meuraxa Banda Aceh tahun 2022 - Nurhayati Nurhayati; Asniah Syamsuddin; Meutia Yusuf; Rahmah Liya Sapitri (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: physical conditions can affect patients in forming their self-concept, patients who have a good self-concept will respect themselves, accept themselves, and do not underestimate themselves and recognize their limitations. Conversely, patients who have a poor self-concept will generally avoid their environment, tend to be alone and dissatisfied with themselves.Objectives: to determine the relationship between self-concept and coping mechanisms in postoperative glaucoma patients at the Eye Clinic at Meuraxa Hospital, Banda Aceh.Methods: this type of quantitative research with the correlation method and using the Cross Sectional Study approach. Sampling using non-probability sampling with purposive sampling technique. The number of samples was 39 patients who underwent glaucoma surgery.Results: the results of bivariate analysis showed the value of ρ = 0.002 and α = 0.05, which means that the value of p < α Ho was rejected and Ha was accepted. This means that there is a relationship between self-concept and coping mechanisms in postoperative glaucoma patients at the Eye Clinic at Meuraxa Hospital.Conclusion: that the better the patient's self-concept, the coping used is adaptive.